Pengaruh Efektifitas Pengendalian Internal dan Moralitas Individu Terhadap Kecenderungan Kecurangan Di LPD Se-Kecamatan Melaya Kabupaten Jembrana - Ni Luh Putu Ayu Remy Octaviani; Ni Putu Ayu Kusumawati; Ni Wayan Alit Erlina Wati (UNHI Press, 2023)
Cheating propensity is a situation where the likelihood of cheating is very high and the consequences are detrimental to othersThis study was conducted in the Melaya District of Regency Jembrana to determine the relationship between the effectiveness of internal controls and the morale of individuals who are prone to misbehavior in LPD. This study uses all his LPD staff as the study population, a total of 71 samples, and study data are analyzed using multiple linear regression methods. The results of this study show that improving internal controls and employee morale can reduce an organization's exposure to fraud. In the future, LPD should improve the internal control system within the organization. Strict sanctions should be implemented for violations occurring within the organization so that employees have a deterrent and good work discipline is established.